2013
DOI: 10.1002/ajmg.b.32128
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the 5‐hydroxytryptamine (serotonin) Receptor 1B gene (HTR1B) with alcohol, cocaine, and heroin abuse

Abstract: Abnormal serotonergic pathways are implicated in numerous neuropsychiatric disorders including alcohol and drug dependence (abuse). The human 5-hydroxytryptamine (serotonin) receptor 1B, encoded by the HTR1B (5-HT1B) gene, is a presynaptic serotonin autoreceptor that plays an important role in regulating serotonin synthesis and release. Although there was evidence of associations of the HTR1B gene variants in the etiologies of substance use disorders, negative findings were also reported. To clarify the roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 63 publications
(100 reference statements)
1
38
0
1
Order By: Relevance
“…In a Chinese Han population, rs11568817 was significantly associated with suicidal behavior in individuals experiencing major depression (Wang et al, 2009). Although conflicting findings exist, a recent meta-analysis concludes that there is a statistically significant association between rs130058 and rs11568817 and alcohol, cocaine, and heroin dependence (Cao, LaRocque, & Li, 2013). …”
Section: Potential Candidate Single Genes For Spirituality and Depresmentioning
confidence: 99%
“…In a Chinese Han population, rs11568817 was significantly associated with suicidal behavior in individuals experiencing major depression (Wang et al, 2009). Although conflicting findings exist, a recent meta-analysis concludes that there is a statistically significant association between rs130058 and rs11568817 and alcohol, cocaine, and heroin dependence (Cao, LaRocque, & Li, 2013). …”
Section: Potential Candidate Single Genes For Spirituality and Depresmentioning
confidence: 99%
“…Numerous studies have identified a number of single nucleotide polymorphisms that are associated with alcohol dependence and/or drug codependence including (a) CHRM2 (Luo et al, 2005; Wang et al, 2004), CHRNA4 (Kim et al, 2004), CHRNA5 (Saccone et al, 2007; Wang et al, 2009) as well as the CHRNA5-CHRNA3-CHRNB4 cluster and alcohol abuse/dependence (Schlaepfer et al, 2008); (b) DAT (Heinz, Goldman, Gallinat, Schumann, & Puls, 2004; see also Bhaskar & Kumar, 2014 for this and other DA-associated polymorphisms), DA beta hydroxylase (DBH) and alcohol dependence in women (Preuss et al, 2013), DRD3 and alcohol craving (Agrawal et al, 2013) as well as DA dysfunction and Cloninger Type I alcoholism (Leggio & Addolorato, 2008); (c) GABRA1, GABRA2, GABRB3, GABRG3 and alcohol dependence or sensitivity to its intoxicating effects during the ascending slope of the BAC curve (e.g., Bierut et al, 2010; Dick et al, 2004; Dick et al, 2006; Edenberg et al, 2004; Enoch, Schwartz, Albaugh, Virkkunen, & Goldman, 2006; Haughey et al, 2008; Noble et al, 1998); (d) GRIK3 (Grzywacz, Malecka, Suchanecka, Bienkowski, Samochowiec, 2013) and GRIN2A (Domart et al, 2012) with alcohol dependence as well as GRM8 and event-related potential (ERP) theta power and alcohol dependence (Chen et al, 2009); (e) 5HT dysfunction and Cloninger Type II alcoholism (Leggio & Addolorato, 2008), HTR1A and alcohol as well as nicotine co-dependence (Zuo et al, 2013), HTR1B and alcohol as well as multiple drug abuse (Cao, LaRocque, & Li, 2013; Contini et al, 2012), HTR2A and alcohol as well as heroin abuse (Cao et al, 2014), HTR7 and alcohol dependence as wel as electrophysiological measures (Zlojutro et al, 2010; Zuo et al, 2014), alcohol dependence and SERT (e.g., Heinz et al, 2004; c.f., Johnson, 2010; McHugh, Hofman, Asnaani, Sawyer, & Otto, 2010; Plemenitas et al, 2015); (f) OPRM1 and level of response to ethanol in Native Americans (Ehlers, Lind, & Wilhelmsen, 2008), OPRM1 polymorphisms and naltrexone’s efficacy for treating alcohol dependence (e.g., Jonas et al, 2014), as well as PDYN and OPRK1 with alcohol dependence (Gerra et al, 2007; Williams et al, 2007; Xuei et al, 2006); (g) CRFR1 polymorphism with P3 ERP and alcohol dependence (Chen et al, 2010); and (h) NPY and its receptor’s association with alcohol as well as multiple drug abuse and dependencies (Bhaskar et al, 2013; Frances et al, 2011; Okahisa et al, 2009; Sato et al, 2010; Wether...…”
Section: Pharmacogenomics and Alcoholism/addictionmentioning
confidence: 99%
“…Genetic studies implicate a link between 5-HT 1B Rs and substance abuse (Cao et al, 2013; Drago et al, 2010; Hasegawa et al, 2002; Huang et al, 2003; Proudnikov et al, 2006; Sun et al, 2002); but see (Cigler et al, 2001; Proudnikov et al, 2006), suggesting that the dysregulation of 5-HT 1B Rs may be a critical part of substance abuse pathology. 5-HT 1B Rs are terminal autoreceptors on 5-HT neurons (Boschert et al, 1994; Doucet et al, 1995; Voigt et al, 1991), as well as heteroreceptors on medium spiny GABAergic neurons originating in striatum and projecting to the ventral pallidum, ventral tegmental area (VTA), and substantia nigra (Bruinvels et al, 1994; Ghavami et al, 1999; Riad et al, 2000; Sari et al, 1997; Sari et al, 1999).…”
Section: Dysregulation Of 5-ht1brsmentioning
confidence: 99%